An Assessment of the Impact and Benefits of Total Productive Maintenance (TPM) On Manufacturing Profitability: A Case Study of a Food Processing Industry in Nigeria (International Journal of Engineering and Computer Science, 2020)
This study was carried out to assess the impact and benefits of Total Productive Maintenance on manufacturing profitability awareness for Grand Cereals Ltd., Jos-Nigeria). The research objective is to assess the impact and benefits of TPM on manufacturing profitability of the company. Data relevant to the study were collected using designed questionnaire, structured interviews, direct observations and company records. The Statistical Package for Social Sciences (SPSS) and Microsoft Excel were used in analysing the data obtained. The results show that the frequency of machine and equipment breakdowns is 58% often and 42% rarely. The research also reviewed that 84% of machine operators were not involved in maintenance activities with only 16% involvement. As regards to the effectiveness of the maintenance technique(s) used, 76% was rated good while 24% was rated fair. Cereal Mill Overall Plant Effectiveness (OPE) was obtained at 38% which was below the world class standard by almost 50%. Equipment downtime was a major cause of plant underutilization with 91% caused by shortage of critical spare parts and 9% shortage of raw materials. On TPM awareness, 80% of the employees have been aware of the TPM concept while 98% indicated the concept of TPM would help improve the current maintenance system and 2% were not sure.20% of the employees were not aware of TPM while 80% of employees indicated that the company does not implement TPM, with 20% not sure that the TPM concept can help improve the current maintenance system. Based on these results, knowledge and information sharing, operator involvement, engagement of all employees from top management to lower level and training should be considered. The effective implementation of TPM model could increase the competition of the company in the dynamic business environment. Thus, adoption and effective implementation of TPM is recommended for the company towards achieving improvement in its manufacturing profitability.